2015
DOI: 10.1093/conphys/cou062
|View full text |Cite
|
Sign up to set email alerts
|

Physiological effects of heat stress on Hawaiian picture-wingDrosophila: genome-wide expression patterns and stress-related traits

Abstract: Two Hawaiian picture-wing Drosophila differ in their temperature tolerances with the ecologically rare species, D. silvestris, showing reduced survival, reduced sperm mobility and greater gene expression changes at high temperatures compared to the common D. sproati. Thus the rare species may have reduced capacity to adapt to future climate changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…HSPs and their cognates are part of the protein quality system that assists in degradation of denatured or aggregated proteins and is mounted when organisms are exposed to environmental stressors, including oxidative, physical activity, heavy metals, and temperature (Sørensen, Kristensen, & Loeschcke, ). We found that genes HSP23 and HSP83 were differentially expressed in low‐and high‐elevation D. sproati populations, and heat‐shocked D. sproati (Uy et al, ) , D. silvestris (Uy et al, ), and D. melanogaster (Leemans et al, ; Sørensen et al, ). Also notable were two DEGs belonging to the HSP70 superfamily that showed differential expression in heat‐shocked D. melanogaster: HSC70–3 (Leemans et al, ) and HSC70Cb (Sørensen et al, ).…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…HSPs and their cognates are part of the protein quality system that assists in degradation of denatured or aggregated proteins and is mounted when organisms are exposed to environmental stressors, including oxidative, physical activity, heavy metals, and temperature (Sørensen, Kristensen, & Loeschcke, ). We found that genes HSP23 and HSP83 were differentially expressed in low‐and high‐elevation D. sproati populations, and heat‐shocked D. sproati (Uy et al, ) , D. silvestris (Uy et al, ), and D. melanogaster (Leemans et al, ; Sørensen et al, ). Also notable were two DEGs belonging to the HSP70 superfamily that showed differential expression in heat‐shocked D. melanogaster: HSC70–3 (Leemans et al, ) and HSC70Cb (Sørensen et al, ).…”
Section: Discussionmentioning
confidence: 87%
“…These include 13.5% of the 74 heat‐shock‐inducible genes in identified by Leemans et al, and 15.6% of the 199 heat‐responsive genes identified by Sørensen et al, , both in D. melanogaster . Our data set also includes 20.1% of 106 DEGs identified within D. sproati subjected to a one‐hour treatment at 25 ° C, as compared to those at a controlled temperature of 16 ° C, and 18.3% of 246 DEGs found in D. silvestris after the same one‐hour, 25 ° C treatment (Table , Uy et al, ). That certain genes were differentially expressed across multiple Drosophila temperature treatment studies and between our low‐ and high‐elevation population groups suggests these genes have important roles in adaptation to thermal conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All parental, F 1 and BC populations were maintained in a controlledenvironment room maintained at a constant 18°C, 70% relative humidity with a 12:12 light/dark cycle. This is a standard environment for rearing Hawaiian Drosophila (Uy et al, 2015) with a generation time of ∼ 3-4 months. Adults were housed in 4-l glass jars with a damp fine sand floor and containing 3 to 5 vials of adult food.…”
Section: Introductionmentioning
confidence: 99%